In Search of Identity: Burgenland-Croatian Perspective - Ščukanec, Aleksandra (2013)
Our paper aims to give an insight into the strategies of identity construction in Burgenland-Croatian community. Special attention is given to the interplay between two i.e. several perspective on the issue in question: Burgenland-Croatian and the outsiders' perspective(s).